2016
DOI: 10.1093/nar/gkw473
|View full text |Cite
|
Sign up to set email alerts
|

Widespread transcriptional gene inactivation initiated by a repair intermediate of 8-oxoguanine

Abstract: DNA damage can significantly modulate expression of the affected genes either by direct structural interference with transcription components or as a collateral outcome of cellular repair attempts. Thus, DNA glycosylases of the base excision repair (BER) pathway have been implicated in negative transcriptional response to several spontaneously generated DNA base modifications, including a common oxidative DNA base modification 8-oxoguanine (8-oxoG). Here, we report that single 8-oxoG situated in the non-transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
91
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(99 citation statements)
references
References 45 publications
7
91
1
Order By: Relevance
“…For example, when OG is located in recognition elements of nuclear factor kappa-light-chain enhancer of activated B cells (NF-κB) (1), specificity protein 1 (SP1) (2), or CAMP responsive element binding protein 1 (CREB) (3) transcription factors, protein-binding affinity was significantly reduced. When OG was present in the template strand of proteincoding regions, modest stalling of RNA pol II occurred (4), whereas initiation of DNA repair at OG to yield an abasic site (AP) stopped RNA pol II, leading to truncated transcripts (5). These observations support a hypothesis of OG decreasing gene transcription.…”
mentioning
confidence: 59%
“…For example, when OG is located in recognition elements of nuclear factor kappa-light-chain enhancer of activated B cells (NF-κB) (1), specificity protein 1 (SP1) (2), or CAMP responsive element binding protein 1 (CREB) (3) transcription factors, protein-binding affinity was significantly reduced. When OG was present in the template strand of proteincoding regions, modest stalling of RNA pol II occurred (4), whereas initiation of DNA repair at OG to yield an abasic site (AP) stopped RNA pol II, leading to truncated transcripts (5). These observations support a hypothesis of OG decreasing gene transcription.…”
mentioning
confidence: 59%
“…1) [11, 33]. Accordingly, we next synthesized catalytically competent, yet stable, AP analogs (tetrahydrofuran, F) in the reporter plasmids and then transfected them into MEF and glioblastoma cells.…”
Section: Og Activates Mrna Synthesis By Facilitating Promoter G-qumentioning
confidence: 99%
“…The Hanawalt laboratory found OG in template strands slightly inhibited advancement of RNA pol II and recruits the transcription-coupled repair machinery slowing transcription [10, 47]; additionally, this work concluded that the AP site generated by OGG1 release of OG blocked transcription and initiated transcription-coupled repair. The Khobta laboratory identified that OG is a barrier to transcription when located in either the coding or template strand in a gene coding region [11, 48]. Further, OG is only a transcriptional barrier after conversion to an AP site by OGG1.…”
Section: Other Examples Of Og As An Epigenetic-like Dna Base Modifmentioning
confidence: 99%
See 2 more Smart Citations